2001
DOI: 10.1074/jbc.m107425200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Respiratory Chain Adjustment to Cellular Energy Demand

Abstract: Because adaptation to physiological changes in cellular energy demand is a crucial imperative for life, mitochondrial oxidative phosphorylation is tightly controlled by ATP consumption. Nevertheless, the mechanisms permitting such large variations in ATP synthesis capacity, as well as the consequence on the overall efficiency of oxidative phosphorylation, are not known. By investigating several physiological models in vivo in rats (hyper-and hypothyroidism, polyunsaturated fatty acid deficiency, and chronic et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 52 publications
4
32
0
1
Order By: Relevance
“…Activation of mitogenesis was observed under various conditions to modestly disturb the mitochondrial oxidative phosphorylation system. 34 Severe injury to the pulp cells and their membrane structures seems unlikely in our study because if that were to occur, AST would be released from mitochondria and cells and, accordingly, its activity would be decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of mitogenesis was observed under various conditions to modestly disturb the mitochondrial oxidative phosphorylation system. 34 Severe injury to the pulp cells and their membrane structures seems unlikely in our study because if that were to occur, AST would be released from mitochondria and cells and, accordingly, its activity would be decreased.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased enzymatic activity observed in our study might be due to orthodontic force-induced proliferation of pulp cells and activation of mitogenesis. 34 Oxygen is essential for the aerobic production of sources of cellular energy such as adenosine triphosphate (ATP) in mitochondria. One in vitro study of pulp cell responses to hypoxia 35 has suggested that hypoxia might enhance the mitochondrial function and proliferative activity of pulp cells in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrion metabolism permits to adequately match ATP synthesis to cellular energy demand according to physiological and/or pathological constraints. This adaptation occurs not only in terms of changing the activity of oxidative phosphorylation pathway, but also in terms of efficiency of this pathway, mitochondrial ATP production being a permanent compromise between rate and efficiency [4].…”
Section: Introductionmentioning
confidence: 99%
“…Such effects are reminiscent to those observed with hyperthyroidism. 17 However, we have previously reported that neither triiodithyronine (T3) nor thyroxine (T4) plasma levels were modified in Lou/C rats. 15 The effects of thyroid hormones are, however, dependent on the quantity of the hormone that reaches peripheral tissues and the availability of thyroid receptors in cell nuclei.…”
Section: Discussionmentioning
confidence: 97%
“…17 J O2 was measured as described above in a medium containing 125 mM KCl, 1 mM EGTA, 5 mM Tris-Pi, 20 mM Tris-HCl, 0.1% fat-free BSA (pH 7.2), and were modulated by addition of increasing concentrations of hexokinase.…”
Section: Mitochondrial Oxygen Consumptionmentioning
confidence: 99%